DETERMINING THE REASONS OF EDUCATION STAFF TO PREFER PARTICIPATION BANKS: THE EXAMPLE OF AKSARAY (Third Sector Social Economic Review, 2023)
Today, it is seen that there are developments in the services of participation banks. In addition to the increase in the number of branches of banks, the variety of services they offer is also increasing and there are intense competition conditions in the banking sector as in all businesses. In order to adapt to the competitive conditions in the banking sector, one of the most important factors that will carry the banks to success is customer satisfaction. For this reason, in this study, the reasons for the education employees to prefer participation banks were investigated.The reasons for choosing participation banks may differ according to the customer profile. In this study, education employees were chosen as the customer profile. The reason why education staff are preferred is that there has not been any study yet on education staff regarding the preference of participation banks in the domestic and foreign literature examined. Thus, it is estimated that the study carried out with the sample used will benefit the literature.The sample of the research consists of 502 education staff working in Aksaray and determined by random method. The scale of the study was developed from the studies of Anaç (2015) and Arpacik (2019).The reliability of the scale used in the study was measured with the Cronbach's Alpha coefficient and was found to be 0.980. This means that the scale is a highly reliable scale. In addition, the values of kurtosis and skewness and the reliability coefficient were examined and it was seen that the result was between -3 and +3. This result reveals that the scale has a normal distribution. Then, exploratory factor analysis was used to determine the construct validity of the scale in the study. Whether the scale was suitable for factor analysis was determined by KMO and Bartlett tests. As a result of this test, it was concluded that the data were suitable for factor analysis. In order to determine the dimensions in factor analysis, a Scree Plot graph was made and it was decided that the scale showed a two-factor structure. The first factor of the scale, which consists of two factors, was determined as ""Products and Services"" and the second factor was determined as ""Being a Participation Bank"". Therefore, it has been observed that education staff give importance to the factors of ""Products and Services"" and ""Being a Participation Bank"" while choosing participation banks.
Keywords: Participation Banking; Education Staff; Islamic Finance; Factor Analysis